PRAKTEK KOLABORASI DOKTER-PERAWAT TERHADAP KEPUASAN KERJA DOKTER UMUM DI RSUD NGANJUK - Galuh Pradhi Paramita; Elsye Maria Rosa (Universitas Muhammadiyah Yogyakarta, 2014)
Background: RSUD Nganjuk is a type B hospital. Patient care in RSUD Nganjuk inpatient unit is done by group of specialists from different disciplines, general practitioners, nurses, and other health personnel. But there are still many obstacles that occur in collaborative practice. Physician-Nurse interactions affect the quality of collaboration practices and physician’s job satisfaction. Method: The study is a quantitative study with cross sectional approach. Populations consisted of all physicians in RSUD Nganjuk. The sampling method used in this study is total sampling. There are 18 respondents. Analysis of the data using multiple linear regression statistical test. Result and Discussion: The result of this study showed the value of F calculating (7,75) > t table value (4,221), and probability value was 0,02. That’s means that the physician-nurse collaboration significantly influences physician’s job satisfaction. Regression equivalent showed: Y = 0,267 X1 + 0,078 X2 + 0,452 X3 + 0,470 X3.Whereas determinant coefficient 0,614. This implied that physician-nurse collaboration simultaneously influence as much as 61,4% to physician’s job satisfaction. Physician-nurse collaboration variable practice that influence physician’s job satisfaction is mutual interest (p=0,03) The other factor: communication (p=0,17), scope of practice (p=0,77), and common goal (p=0,05) has not yet been influence in physician’s job satisfaction. Conclusion: There was a significant influence among the collaboration variable practice consisting of communication (X1), the scope of practice (X2), mutual interests (X3), and a common goal (X4) simultaneously on physician’s job satisfaction at the inpatient unit of RSUD Nganjuk. The most influential factor is the common goal.